Obliquely incident laser and electron beam interaction in an undulator - Xiaofan Wang; Chao Feng; Cheng-Ying Tsai; Li Zeng; Zhentang Zhao (Physical Review Accelerators and Beams, 2019)
The angular drift of a laser beam is of particular concern in applications such as seeded free-electron lasers. A systematical study of the obliquely incident laser and electron beam interaction in an undulator is presented in this paper. Theoretical analysis and numerical simulations demonstrate that the interaction would imprint energy and angular modulations on the electron beam simultaneously. Compared with the normally incident pattern, the obliquely incident laser-electron interaction leads to reductions in the bunching factors of HGHG and EEHG. In the meanwhile, proactive applications of this multidimensional modulation technique may bring vitality to the field of laser-electron manipulation.